Development of board game as teaching aids for basic electronics courses - Zubaidah Abdul Rahman; Rasmaliza Rashid; Siti Sarah Malini Mohd Hanifa (Journal of Counseling and Educational Technology, 2022)
A variety of teaching methods can help increase students' interest and focus on a subject. A game -based learning approach is suitable to be used by students for them to enhance their problem solving skills directly or indirectly during the game session. The students have difficulty remembering and understanding the symbols, structures and functions of electronic components causing them failed to answer assessment questions well. This teaching aids are specifically designed to enhance students’ understanding of basic electronics courses that have a variety of name, symbols, structure and functions to remember. Also suitable use during learning sessions because it can increase students' understanding through rapid learning and revision while playing. Due to limited electronic-based board games in the market, The Components was suggested as one of the learning tools, especially in the field of electrical engineering.